Hidden diversity in Mexico: Akorhexoza tariacurii sp. nov. (Diptera: Scatopsidae) and new records of minute black scavenger flies - Huerta, Heron; Guarin-Anacona, Andres; Cultid-Medina, Carlos Andres (Zootaxa, 2025)
We describe and illustrate a new species of the genus Akorhexoza Cook, Akorhexoza tariacurii sp. nov., closely related to two previously known species from Mexico: A. cactivora Cook and A. dampfi (Duda). A key to the species is provided, along with the first records of Coboldia fuscipes (Meigen) and Holoplagia guamensis (Johannsen) in Mexico, and new distribution records for Akorhexoza cactivora Cook, Akorhexoza dampfi (Duda), Aztecatopse diabolica (Duda) and Swammerdamella marginata Cook. Additionally, a comprehensive list of all known species of the family Scatopsidae in Mexico and their state-level distributions is included.